Ethnomedicinal uses of plants by Santal Tribal peoples at Nawabganj upazila of Dinajpur district, Bangladesh (Bangladesh Journal of Plant Taxonomy, 2019)
Ethnobotanical investigation on traditional medicinal plants used by Santal tribal people of Nawabganj upazila of Dinajpur district, Bangladesh was documented. Frequent field trips were made during January to December 2018 to record ethnobotanical data by interviewing Santals of various age group, mostly ranging between 20-76 years, including the traditional healers. A total of 105 plant species under 97 genera belonging to 57 families were recorded which are used by the Santals for the treatment of 67 ailments. Out of these plant species 44% belonged to herbs, 28% trees, 18% shrubs, 10% climbers. In herbal formulations, leaves were found to be mostly used (29%) followed by roots (12%), fruits (12%), whole plant (10%), seeds (9%), barks (9%), stems (5%), flowers (4%), latex (2%), rhizomes (2%), petioles (2%), gums (2%), bulbs (1%), tubers (1%), pods (1%) and buds (1%). The Santal medicinal wealth have been presented with scientific name, family, Bangla name, Santal name, part(s) used, ailments to be treated and formulations. This study also provides data on diversity, distribution and habitats for conservation and prioritization of the medicinal plants.